ANALYSIS OF CARRYING CAPACITY AND LAND SUITABILITY FOR THE DEVELOPMENT OF CATTLE-BASED AGROSILVOPASTORAL SYSTEMS IN TALUDITI SUBDISTRICT - Diko, Abdullah Kadir; Lihawa, Fitryane; Baderan, Dewi Wahyuni K (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Agro-silvopastoral systems, which integrate trees, crops, and livestock within the same landscape, are increasingly promoted as context-specific strategies for sustainable rural development in regions facing high land-use pressure and climate variability. This systematic review synthesises evidence on how such systems perform in terms of environmental outcomes, livelihoods and economic viability, and social and governance dimensions, and how these dimensions interact. A structured search and screening procedure was applied to peer-reviewed and grey literature on agro-silvopastoral and related agroforestry systems. The final sample of studies was thematically coded across four analytical themes: typologies and design configurations, environmental performance and ecosystem services, livelihoods and economic outcomes, and governance, institutions, and scaling pathways. The findings indicate that diverse agro-silvopastoral typologies, including homegardens, alley-cropping, silvopastoral pastures, and multi-strata systems, mobilise ecological mechanisms such as niche complementarity, nutrient cycling, and microclimate regulation. Empirical studies consistently report improvements in soil fertility, erosion control, water regulation, biodiversity, and carbon sequestration relative to conventional monocultures. These environmental benefits are closely associated with enhanced net income, favourable benefit–cost ratios, labour productivity, income diversification, and improved food security, thereby contributing to household resilience. However, the distribution of benefits is uneven, as poorer households, landless farmers, women, and other marginalised groups often face barriers to participation and may receive a smaller share of gains. Governance configurations, including community-based management, co-management, cooperatives, extension services, and policy incentives, emerge as decisive factors in enabling adoption, coordinating actors, and scaling successful models. Overall, the review concludes that agro-silvopastoral systems hold substantial potential as climate-resilient, multifunctional land-use strategies, but their outcomes depend on context-appropriate design and supportive, inclusive governance and institutional arrangements. Future research should employ integrated, mixed-methods approaches to jointly assess ecological, economic, and social equity dimensions and to compare alternative policy and governance configurations. Keywords: agro-silvopastoral systems; agroforestry; ecosystem services; rural livelihoods; collaborative governance; climate-resilient agriculture; sustainable rural development.